Effects of supercharge pressure on combustion characteristics of a diesel rngine fueled with alcohol–diesel blends - SAYIN, CENK (My University, 2023)
© 2023, King Fahd University of Petroleum & Minerals.The recent increase in diesel prices is the most crucial factor that maintains alternative fuel research on the agenda in diesel engines. This study aims to analyze the combustion characteristics of ethanol–butanol–diesel triple-fuel mixtures and to investigate the effects of the boost pressure in a single-cylinder diesel engine. In the engine test, while the boost pressure at 1600 rpm was fixed at 240 mbar, the intake air pressure gauge was increased to 264, 228, and 312 mbar. As a result of the study, the most prolonged combustion duration in all test conditions was obtained using pure fossil diesel fuel. More than a 10% increase in ignition delay times has been calculated for blends. In addition, significant increases were observed in the heat release rate as the alcohol content in the blends increased. While considerable reductions in CH4, CO, and CO2 emissions were monitored by using the alcohol–diesel mixtures with the increased boost pressure, the stable formation in NOx emissions was not observed. Moreover, there was a significant increase in combustion noise with alcohol–diesel blends.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Alcohol fuels; Boost pressure; Combustion; Diesel engine; Exhaust emission; Boost pressure; Alcohol fuels; Diesel engine; Combustion; Exhaust emission